Global Pentecostal movements: migration, mission, and public religion - Wilkinson, Michael (International studies in religion and society, 2012)
Preliminary Material -- The ‘Many Tongues’ of Global Pentecostalism /Michael Wilkinson -- Pentecostals and Political Culture in Sub-Saharan Africa: Nigeria, Zambia, and Kenya as Case Studies /Richard Burgess -- Pentecostalism and the Challenges Facing Muslim-Christian Relations in Nigeria /A. Christian van Gorder -- Global Pentecostal Networks and the Problems of Culture: The Church of Pentecost in Ghana and Abroad /Girish Daswani -- From Bethel Temple, Seattle to Bethel Church of Indonesia: Missionary Legacy of an Independent Church /David A. Reed -- Resisting Globalization: The Pentecostal Holiness Church’s Mission and the ‘Anti-Christian Movement’ in China (1920–30) /Connie Au -- The Role of American Evangelist Tommy Hicks in the Development of Argentine Pentecostalism /Seth N. Zielicke -- A New Kind of Ministry for a New Kind of Context: The Rise of New Indigenous Churches in West Africa /Joseph Bosco Bangura -- Standing at the Crux: Pentecostalism and Identity Formation in an African Diaspora Christian Community /Thomas Aechtner -- Becoming Pastora: Latina Pentecostal Women’s Stories from Newark, New Jersey /Otto Maduro -- Hybridity, Migration, and Transnational Relations: Re-thinking Canadian Pentecostalism from a Latina/o Perspective /Néstor Medina -- Index.